Analysis of the principle of Asbāb al-Nuzūl and its implications for social exegesis: A study of QS. An-Nisā’ [4]:58 and QS. al-Ḥujurāt [49]:9 in Tafsir al-Jalālain - Indah Purnama Sari; Mutiara Kasih; Hidayatullah Ismail (Privietlab, 2025)
The Qur’an serves as a comprehensive guide for life, directing spiritual aspects and regulating the social dimensions of human existence. To grasp its universal messages comprehensively, an asbāb al-nuzūl approach is essential, as it traces the historical context of the revelation. This study examines the application of the asbāb al-nuzūl concept in Tafsir al-Jalālain by Jalāl al-Dīn al-Maḥallī and Jalāl al-Dīn al-Suyūṭī and its relevance to the formation of social interpretation, particularly concerning QS. An-Nisā’ [4]:58 and QS. al-Ḥujurāt [49]:9. Employing a qualitative-descriptive approach through library research, this study explores the exegetes’ interpretive patterns. The findings indicate that Tafsir al-Jalālain employs asbāb al-nuzūl not only to explain the causes of revelation but also to affirm broader moral and social meanings. QS. An-Nisā’ [4]:58 emphasizes the values of trustworthiness and justice in public leadership, while QS. al-Ḥujurāt [49]:9 highlights the importance of reconciliation in mitigating social conflicts. The application of the principle al-‘ibrah bi ‘umūm al-lafẓ lā bi khuṣūṣ as-sabab universalizes the message of the verses, making them relevant across the ages. Thus, Tafsir al-Jalālain is not only a concise exegesis (tafsīr ijmālī) but also contributes significantly to shaping a contemporary paradigm of social interpretation that resonates with modern reality.